Infectivity assay for detection of SARS‐CoV‐2 in samples from patients with COVID‐19. Issue 10 (29th June 2021) - Hiroi, Satoshi; Kubota‐Koketsu, Ritsuko; Sasaki, Tadahiro; Morikawa, Saeko; Motomura, Kazushi; Nakayama, Emi E.; Okuno, Yoshinobu; Shioda, Tatsuo
Abstract: Since the coronavirus disease 2019 (COVID‐19) outbreak, laboratory diagnosis has mainly been conducted using reverse‐transcription polymerase chain reaction (RT‐PCR). Detecting the presence of an infectious virus in the collected sample is essential to analyze if a person can transmit infectious severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). However, there have been no quantitative investigations conducted for infectious SARS‐CoV‐2 in clinical samples. Therefore, in the present study, a rapid and simple focus‐forming assay using the peroxidase‐antiperoxidase technique was developed to quantify infectious SARS‐CoV‐2 titers in 119 samples ( n = 52, nasopharyngeal swabs [NPS]; n = 67, saliva) from patients with COVID‐19. Furthermore, the study findings were compared with the cycle threshold (Ct) values of real‐time RT‐PCR. The infectious virus titers in NPS samples and Ct values were inversely correlated, and no infectious virus could be detected when the Ct value exceeded 30. In contrast, a low correlation was observed between the infectious virus titers in saliva and Ct values (r = ‐0.261, p = 0.027). Furthermore, the infectious virus titers in the saliva were significantly lower than those in the NPS samples. Ten days after the onset of COVID‐19 symptoms, the infectious virus was undetectable, and Ct values were more than 30 in NSP and saliva samples. The results indicate that patients whose symptoms subsided 10 days after onset, with Ct values more than 30 in NSP and saliva samples, were less likely to infect others. Highlights: A rapid and simple focus‐forming assay using the peroxidase‐antiperoxidase technique was developed to quantify infectious SARS‐CoV‐2 titers. Infectious virus titers in NPS samples and Ct values were inversely correlated, and no infectious virus could be detected when the Ct value exceeded 30. In contract, a low correlation was observed between the infectious virus titers in saliva and Ct values. Infectious virus titers in the saliva were significantly lower than that in the NPS samples. Patients whose symptoms subsided 10 days after onset, with Ct values more than 30 in NSP and saliva samples, were less likely to infect others.